Diseño, construcción y montaje de un mezclador y un sistema elevador de agregados pétreos para una planta adoquinera bloquera en la Universidad Nacional de Loja. - González, Telmo (2006)
The present work of grade thesis is based on the design, construction and assembly of a mixer and elevator of stony attachés for a plant adoquinera-bloquera in the National University of Loja, what will allow that this institution can produce blocks and paving stones for internal benefit and of the collective. The exposed machines are conformed by boxcars, axes, crosses, bearings, subjection mechanisms, pinenuts, chain, motoreductores, elevation cable, structures of support, control boards and some auxiliary elements. The calculation of the pieces and elements that conform the machines developed them to him by means of the employment of bibliography of design mechanic and the advice of professionals that are devoted to the production of this machinery. The process of selection of the constituent elements is carried out it with the approaches but appropriate so it guarantees the good design of you scheme them. It is also carried out an environmental and economic valuation to end up obtaining the real cost of the same one.